Otitis Media Among North American Indians ; The Navajo - Joseph L Stewart (Journal of All India Institute of Speech and Hearing, 1970)
Otitis media (OM) is the leading cause for hearing impairment world-wide and is one of the most universal diseases known to Man. It appears that every child in the world will at one time have at least one episode of the acute stage of the disease. In common with othv.r such pervasive diseases, it seems to strike most frequently and most devastatingly those children living in areas where treatment services are remote, in short supply, orotherwise not readily accessible. Recent surveys of the literature, reviewed by Stewart (1985) indicate particularly high prevalences among the  North American Indian and Eskimo  populations, the Aboriginal people of  Australia, and the various island populations in the western and southern Pacific.  While high rates of OM are not limited to these geographical areas, the genetic commonalities of many of them lend even higher support to the roles of anatomical and immunological variables which add to the susceptibility of these people to the disease.